Enhancing Biodegradation of Industrial Wastewater into Methane-Rich Biogas Using an Up-Flow Anaerobic Sludge Blanket Reactor - Lindokuhle Ngema; Devona Sathiyah; Emmanuel Kweinor Tetteh; Sudesh Rathilal (Applied Sciences, 2023)
Anaerobic digestion (AD), the oldest technology used for treating waste, converts organic matter into biogas in the absence of oxygen. The current efforts focuses on improving the digestion of a local industrial wastewater to produce biogas and treat water for reuse. A lab-scale up-flow anaerobic sludge blanket (UASB) reactor operated at 37 °C was employed for the biodegradation the industrial wastewater. A one-factor-at-a-time (OFAT) approach was used to study the effects of influent chemical oxygen demand (CODin), hydraulic retention time (HRT), and magnetic nanoparticles (magnetite) on UASB biogas and COD elimination from digestate wastewater. The optimum HRT for the biodegradation of municipal wastewater was found to be 21 days with contaminants’ removals of 94%, 90.1%, and 98.9% for COD, color, and turbidity, respectively. The addition of magnetite resulted in 225 mL of cumulative biogas produced with 73% methane content, and treatability efficiency of 85%. The most influential factor was magnetite load, which stimulated the microbial activity via redox catalytic reaction in degrading the high organic wastewater (9590 mg COD/L) into biogas production. The prospects of upgrading lab-scale of this technological concept for bioenergy production is viable to mitigate wastewater management and fossil fuel environmental challenges.